1994
DOI: 10.1002/ptr.2650080807
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the serotonergic system in the memory effects of Ginkgo biloba L. and Panax ginseng C. A. Mey

Abstract: The 7-day oral administration of the extracts from Ginkgo biloba (GK501) and Panax ginseng (G115) as well as their combination PHL-00701 (Gincosan@) produced changes in rat behaviour suggesting memory-enhancing effects. Single doses of agonists and antagonists of different serotonin receptor subtypes influenced the rat's capability for retention of learned behaviour and the behavioural effects of the drugs tested. GK501 decreased the density of 5-HT, receptors in the frontal cerebral cortex and hippocampus. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Published trials showing beneficial effects of ginseng include those of D' Angelo et al (1986), demonstrating improvements on motor performance, and Rosenfeld et al (1989), showing benefits on neuropsychological measures. Beneficial effects on memory have also been reported in animals (Petkov et al 1993(Petkov et al , 1994.…”
Section: Introductionmentioning
confidence: 84%
“…Published trials showing beneficial effects of ginseng include those of D' Angelo et al (1986), demonstrating improvements on motor performance, and Rosenfeld et al (1989), showing benefits on neuropsychological measures. Beneficial effects on memory have also been reported in animals (Petkov et al 1993(Petkov et al , 1994.…”
Section: Introductionmentioning
confidence: 84%
“…The present study showed that short-term administration of Ginkgo biloba extract at a dose previously shown to facilitate learning and memory processes in rats (Petkov et al 1993b;Petkov et al 1994) significantly decreased the number of b-adrenergic receptors in the frontal cerebral cortex and hippocampus. This finding is in agreement with the decreased density of b-adrenoreceptors observed in rat cerebral cortex after long-term treatment (27 days and 2 months) with Ginkgo biloba extract (Brunello et al, 1985;Racagni et al 1986).…”
Section: Resultsmentioning
confidence: 82%
“…Thus, Ginkgo biloba extracts exert a complex pharmacological effect in vivo, i.e. an action on b-adrenergic (this study, Racagini et al, 1985), serotonergic (Petkov et al, 1994) and cholinergic (Taylor, 1986) neurotransmission. Finally, it might be suggested that modulation of different brain neurotransmitter systems is responsible for the cognition-enhancing effects of Ginkgo biloba since interactions between cholinergic, noradrenergic and serotonergic neurotransmission have been shown to play important roles in realizing learning and memory events (Wenk et al, 1987).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations